Thermal Overload Relay (TOR) Sebagai Sistem Proteksi Motor Induksi 3 Fasa Pada Mesin Molding Biofuel Pelletizer Di PT. Sejin Lestari Furniture - Tiya Puspita; Ilham Akbar Darmawan (Pusat Riset dan Inovasi Nasional, 2023)
PT. Sejin Lestari Furniture is a company engaged in the production of furniture such as doors, tables, chairs, cabinets, bookcases and other interior equipment. As one of the companies that have succeeded in producing finished goods in large quantities, PT. Sejin Lestari Furniture relies on the help of an electric motor at every stage of its production, including one of the wood pellet production machines, namely the biofuel pelletizer molding machine which has four different types of motors. In order to work optimally, electric motors need a protection system that can protect them from threats. In this study, the protection system used is Thermal Overload Relay (TOR) which functions as an overload controller so that the electric motor is not easily burned or damaged. In this case, the TOR must be adjusted according to the capacity of each induction motor so that when an overload occurs, the TOR will automatically cut off the current flowing in the motor so that damage can be avoided. The TOR trip standards in this study uses the NEMA (National Electrical Manufactures Association) standard with the method used, namely Research and Development (R&D) where this method is carried out to produce certain products and test the effectiveness of these products. The data collection was obtained through journals and books.